Oral Hygiene dalam Pencegahan Ventilator-Associated Pneumonia pada Pasien Kritis: Literature Review - Yuli Wahyu Utami; Beti Kristinawati (Universitas Faletehan, 2022)
Ventilator-associated pneumonia (VAP) can occur in critically ill patients undergoing mechanically ventilated 48 hours after intubation. The incidence of VAP can be prevented by performing a VAP bundle, one of which is by performing oral hygiene using antiseptic ingredients that are effective killing germs. The literature review aims to analyze materials that are effective in performing oral hygiene. A total of 25 articles from 1728 articles were selected in the review. Systematic reviews were carried out using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) reporting technique. Article searches were carried out through the online databases of Pubmed, Scientdirect, and Google Scholar. Articles are limited by type and year (last 10 years), but not by language. The results of the review show that the ingredients used for oral hygiene and proven effective in preventing VAP are ingredients that contain antibacterial and antiseptic. The conclusion of this literature review is that oral hygiene using ingredients that can suppress growth and kill bacteria is proven to prevent the occurrence of VAP.